1999
DOI: 10.1002/(sici)1099-1352(199901/02)12:1<57::aid-jmr444>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and characterisation of affinity ligands for glycoproteins

Abstract: The concepts of rational design and solid phase combinatorial chemistry were used to develop affinity adsorbents for glycoproteins. A detailed assessment of protein-carbohydrate interactions was used to identify key residues that determine monosaccharide specificity, which were subsequently exploited as the basis for the synthesis of a library of glycoprotein binding ligands. The ligands were synthesised using solid phase combinatorial chemistry and were assessed for their sugar-binding ability with the glycoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The introduction of these ligands can lead to more efficient, less expensive, and safer procedures for antibody purification at manufacturing scales. Among those protein A mimetics like A2P [25][26][27][28], D-PAM [29][30][31][32], hexamer peptide ligands [33] and CaptureSelect ® [34] have been the subject of intense investigation.…”
Section: Ligandsmentioning
confidence: 99%
“…The introduction of these ligands can lead to more efficient, less expensive, and safer procedures for antibody purification at manufacturing scales. Among those protein A mimetics like A2P [25][26][27][28], D-PAM [29][30][31][32], hexamer peptide ligands [33] and CaptureSelect ® [34] have been the subject of intense investigation.…”
Section: Ligandsmentioning
confidence: 99%
“…A common strategy for establishing a small but promising library is to choose the functional groups that chemically and structurally complement the target protein (Palanisamy et al, 1999;Sproule et al, 2000;Platis et al, 2006). For instance, in order to develop affinity ligands for human insulin precursor, Sproule et al (2000) examined the structure of the protein and identified a possible binding region for ligands, which contains several aromatic residues.…”
Section: Library Establishmentmentioning
confidence: 71%
“…This approach is especially applicable to libraries established by solid synthesis, of which the ligands are already immobilized. Lowe and co-workers (Palanisamy et al, 1999;Teng et al, 1999;Sproule et al, 2000;Roque et al, 2005;Platis et al, 2006) screened affinity ligands for various proteins by chromatographic methods. However, the scale of chromatographic evaluation is usually limited.…”
Section: Library Screeningmentioning
confidence: 99%
“…To design a ligand with promising affinity to the target peptide, the first principle is to identify a target binding site or use a known biological interaction as a template which was suggested by Lowe and coworkers [31,44,45]. According to our previous data, two tryptophan residues (Trp) on the C-terminal of VW-8 were the main binding sites, and the ligands bearing both hydrophobic and electrostatic sites probably exhibited higher affinity to VW-8 [37,38].…”
Section: Resultsmentioning
confidence: 99%